Development of Maths Booklet Media for Primary School Students - Armayanti, Ayuk; Nasution, Ismail Saleh (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research focuses on the development, validity, and practicality of booklet-based teaching materials for mathematics subjects, specifically on equivalent fractions. Following the Research and Development (R&D) model, which incorporates the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design stages, this research aims to create effective learning aids. The assessment of the developed Booklet showed high validity and practicality. The material expert assessment rated it "very valid" at 93.33%, while the media design and language experts rated it high at 98.57% and 95%, respectively. In addition, both teachers and students considered the Booklet practical, with response percentages of 87% and 94%, respectively. These findings underscore booklet-based learning materials' effectiveness and ease of use in mathematics education. The Booklet is a valuable tool for teachers to deliver curriculum content effectively and for students to improve their understanding of mathematical concepts. Learning outcomes can be significantly enhanced through such media, facilitating understanding and practical application of mathematical principles.